PENGARUH PENGGUNAAN MINYAK ZAITUN BEROZON TERHADAP PERAWATAN KULIT WAJAH KERING - INDRI ALVIONITA ISWANDAR; Linda Rosalina (Jurnal Tata Rias dan Kecantikan, 2022)
This study aims to a) know the descriptive moisture of dry skin in the control group, b) to know the descriptive moisture of dry skin after being given olive oil, c) to know the descriptive moisture of dry skin after being given ozone-treated olive oil, d) to determine the use of ozone-treated olive oil on dry facial skil.This type of research is an experiment. The object of this research is women aged 30- 45 years in the coastal area of West freshwater, Padang city who have dry facial skin. The data collection technique is using 6 samples with purposive sampling technique. Descriptive data analysis techniques and bivariate analysis using ANAVA test with 95% confidence.Based on the results of the study, the average facial skin moisture of the sample from the first day to the 10th day did not change the condition to normal with ordinary facial skin care, the average facial skin moisture of the sample experienced a change on day 6 from very dry to dry facial skin, in The 9th day changes to normal and becomes moist. The day after facial treatment using olive oil is carried out, the average facial skin moisture of the sample changes on day 5 from very dry facial skin to dry, day 6 changes to normal, becomes moist starting from day 5. 7 and lasted until the 10th day after facial treatment using olive oil, the hypothesis "there is a difference in the effect of treatment on dry facial skin conditions with regular facial skin cleansing, skin care with olive oil and facial skin care using olive oil with ozone on facial skin care. dry ”received at a significant level si 95% because Fcount (6,703)> Ftable (3.34), different test states that the results of ordinary facial cleansing of the sample are significantly different, but facial treatments with olive oil without ozone and with ozone are not significantly different. But the result of increasing the moisture process using olive oil with ozone is faster to moisture to facial skin.